Occurrence of CCR5 Heterozygous 32 bp Deletion in Nepali Ethnic Groups - Singh, Nanda Bahadur (Journal of Institute of Science and Technology, 2015)
The Chemokine (C-C) receptor 5 (CCR5) as one of the small signaling proteins, is a HIV-1 resistant gene. The major boosting to the study of CCR5 gene among ethnic groups in the world is the detection of 32 bp deletion in its heterozygous and homozygous condition which is responsible for relative or absolute resistance to HIV-1 infection. A total of 456 samples belonging to six Nepalese ethnic groups were subjected to genotyping by the use of PCR-RFLP for detecting 32 bp deletion on exon 3 of CCR5 gene. Finally, allele frequencies of 32 bp deletion among Nepalese ethnic groups were calculated by the use of Hardy-Weinberg formula for analysis and interpretation. Chidimar ethnic group, for the first time, showed heterozygous 32 bp deletion at the population level in Asia-pacific region is an excitement in which Chidimar might have conferred resistance against HIV-1 infection in Nepal. Journal of Institute of Science and Technology, 2014, 19(2): 105-108